Pengaruh Financial Distress Dan Kepemilikan Manajerial Terhadap Manajemen Laba Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2017-2020 - Putu Ria Monica Sari; Ni Putu Ayu Kusumawati; Ni Wayan Alit Erlina Wati (Hita Akuntansi dan Keuangan, 2023)
This study plans to decide the impact of monetary trouble and administrative proprietorship on the profit the executives of assembling organizations recorded on the Indonesia Stock Exchange in 2017-2020. This exploration is a kind of similar causal examination. The populace in this study were all Manufacturing Companies recorded on the Indonesia Stock Exchange in 2017-2020 upwards of 182 organizations. In light of the testing method utilizing purposive examining, 115 example organizations were gotten from 182 organizations. The information assortment method utilizes optional information from monetary reports distributed on the authority site of the Indonesia Stock Exchange. The scientific method utilized in this exploration is Logistic Regression Analysis. The outcomes showed that there is a positive connection between monetary pain factors on income the executives and there is a negative connection between administrative proprietorship and profit the board.